Telitacicept following plasma exchange in the treatment of subjects with recurrent neuromyelitis optica spectrum disorders: A single‐center, single‐arm, open‐label study. (18th July 2022) - Ding, Jie; Jiang, Xianguo; Cai, Yu; Pan, Shuting; Deng, Ye; Gao, Meichun; Lin, Yan; Zhao, Nan; Wang, Ze; Yu, Haojun; Qiu, Huiying; Jin, Yuyan; et al.
Abstract: Introduction: Neuromyelitis optica spectrum disorders (NMOSD), mainly mediated by B cells and AQP4 antibody, has a high rate of recurrence. Telitacicept is a novel drug specifically targeting the upstream signaling for the activation of B cell with its following production of autoimmune antibodies. Thus, it may be a promising approach. Our study preliminarily explored the potential safety and effectiveness of Telitacicept following plasma exchange in the treatment of recurrent NMOSD. Methods: This was a single‐center, single‐arm, open‐label study enrolling eight patients with recurrent NMOSD in China. All patients received plasma exchange three times, followed by Telitacicept 240 mg every week for 46 times. The primary endpoint was the time of first recurrence after enrollment. Secondary end points included: changes in Expanded Disability Status Scale score, Optic Spinal Impairment Scale score, Hauser Ambulation Index, number of lesions on MRI, retinal nerve fiber layer thickness measured by optical coherence tomography, latency and amplitude of visual evoked potential, titer of AQP4 antibody, and immune parameters of blood. Safety was also assessed. The study was registered with Chictr.org.cn (ChiCTR1800019427). Results: Eight eligible patients were enrolled. Relapse occurred in two patients (25%) and five patients (63%) remained relapse free after 48 weeks of treatment. The time to first recurrence was prolonged and the number of recurrences was reduced ( p  < 0.001, power of test = 1). One patient withdrew from the study due to low neutrophil count. No serious adverse events occurred. Conclusions: In this small, uncontrolled study, Telitacicept following plasma exchange has the potential to be a safe treatment for patients with recurrent NMOSD. It may prolong the recurrence interval and reduces the annual count of recurrences. A multicenter randomized controlled study with a larger sample is thus feasible and needed to further assess its safety and efficacy. Abstract : In this small‐scale study, Telitacicept following plasma exchange has the potential to be a safe and effective treatment for patients with recurrent neuromyelitis optica spectrum disorders (NMOSD). It may prolong the recurrence interval and reduces the annual count of recurrences. Although this work does not draw a definite conclusion concerning the safety and effectiveness, it provides important information of a novel alternative therapeutic strategy for NMOSD with probably better therapeutic potentials but with no safety issues observed so far, worthy of next stage clinical study.